What Does It Take to Become a CPT?. Issue 10 (November 2013) - Houger, Vaughan P.; Roux‐Zink, Mary Rita
Abstract Many performance improvement professionals are considering seeking the Certified Performance Technologist (CPT) certification offered by the International Society for Performance Improvement (ISPI). This article provides an overview of factors for potential CPTs to consider: adherence to the standards and ethics code as well as the interrelationships of professional principles and personality traits. Prospective CPTs are encouraged to include a self‐assessment as part of their considerations related to acquiring CPT certification.